Herd immunity and prevention in HPV transmission with exogenous reinfection. - Md Mehedi Hasan; Md Hamidul Islam (PLoS ONE, 2025)
Cervical cancer is a major global health concern, primarily caused by human papillomavirus (HPV), which spreads through unsafe sexual contact. Natural immunity often fails to provide full protection, permitting exogenous reinfection, which plays a key role in the persistence and transmission of HPV. This paper presents and analyzes a deterministic mathematical model of HPV transmission, incorporating exogenous re-infection. We utilized VIA test result data from 2019 to 2023 in Bangladesh to estimate key parameter values. The findings were validated through numerical simulations using MATLAB, and the analytical results demonstrated strong consistency with the numerical outputs. A critical insight is the presence of reinfection-induced backward bifurcation, indicating that targeting primary infections alone is insufficient for eradication, highlighting the need to address exogenous reinfection for effective control. We propose optimal control strategies tailored to resource-limited settings like Bangladesh, where limited vaccine access presents significant challenges, and community-driven education on safe sexual practices is crucial and continuously evolving. The results emphasize that the most effective approach combines targeted prevention with widespread community education, while precision in intervention implementation is essential to prevent reinfection surges that could prolong disease persistence and undermine control efforts. These insights provide a strong foundation for refining intervention strategies and offer valuable guidance for controlling HPV transmission through non-pharmaceutical interventions, particularly in resource-constrained settings.